Ensuring best E-waste recycling practices in developed countries: An Australian example. (1st February 2019) - Dias, Pablo; Bernardes, Andréa Moura; Huda, Nazmul
Abstract: The waste electrical and electronic equipment (e-waste) management is one of the great challenges faced in the twenty-first century due to the steep e-waste increase worldwide and their potential to be both a source of valuable materials and a hazardous source of contamination. In this study, the management of e-waste is discussed having the Australian recycling scheme as an example. The investigation on the actual recycling process and the associated cost analysis revealed important outcomes for the decision-making process of determining which equipment (or materials) will be exported and which will be recycled domestically. It is shown that scrap computers are the only equipment with enough intrinsic value to justify the domestic recycling without requiring any external subsidy. Furthermore, the importance of such subsidy, of regulations and monitoring are discussed, principally for e-waste with an intrinsic value smaller than computers. The results indicate that labor accounts for more than 90% of the cost of first stage recycling in Australia, which can be extrapolated to countries where labor is expensive. Finally, in the interest of achieving a better waste management worldwide, this study provides arguments to encourage a better monitoring of the recycling processes undertaken internationally and/or the promotion of downstream recycling processes in developed countries. Highlights: The decision making of international over domestic recycling is explained. In developed countries, labor represents >90% of first stage recycling cost. There is no economic incentive for first stage recycling in developed countries. Regulations and monitoring are paramount in ensuring best recycling practices. The subsidy paid by the producers of the waste is crucial to allow WEEE recycling.